2015
DOI: 10.1111/tbj.12416
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Clinical Significance of Sternal Lesions on Breast MRI

Abstract: The purpose of this study is to characterize sternal lesions detected on breast magnetic resonance imaging (MRI), compare MRI detection of sternal lesions with other imaging modalities (bone scan, positron emission tomography/computed tomography (PET/CT) and chest CT), and ascertain how often patient management is altered by discovery of sternal lesions. Retrospective review of 1143 breast MRIs between 2007 and 2012 identified 17 patients with sternal lesions including 15 patients with newly diagnosed breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this series, malignant sternal lesions occurred more frequently in association with aggressive breast cancer and had malignant type dynamics on breast MRI scans. 27 Overall, we had a relatively low rate of EMFs in our study, with a very low rate of malignant EMFs. The greatest portion of EMFs came from women who underwent MRI for evaluation of known breast cancer, although we did have a single patient who underwent an MRI for high risk status and was found to have metastatic disease based on an EMF found on the screening MRI.…”
Section: Discussionmentioning
confidence: 63%
“…In this series, malignant sternal lesions occurred more frequently in association with aggressive breast cancer and had malignant type dynamics on breast MRI scans. 27 Overall, we had a relatively low rate of EMFs in our study, with a very low rate of malignant EMFs. The greatest portion of EMFs came from women who underwent MRI for evaluation of known breast cancer, although we did have a single patient who underwent an MRI for high risk status and was found to have metastatic disease based on an EMF found on the screening MRI.…”
Section: Discussionmentioning
confidence: 63%
“…Schaefer et al reported on 17 patients with a breast cancer diagnosis and MRI‐detected sternal lesions of which 9 proved to be malignant, with MRI making the prospective diagnosis of Stage IV disease in 4 (the remainder with bone metastases already identified by other imaging). They also noted that some metastatic lesions identified by MRI were not evident on either 99mTc‐MDP bone scan or PET/CT 3 …”
Section: Introductionmentioning
confidence: 99%
“…They also noted that some metastatic lesions identified by MRI were not evident on either 99mTc-MDP bone scan or PET/CT. 3 In a more recent study, patients with metastatic lesions detected on either PET/CT or bone scan had their prior breast MRI scans reviewed. Of 14 sternal metastases, Lee et al 4 found that 12 (86%) were retrospectively identifiable on breast MRI, but only 8 (57%) had been prospectively reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation